A Method of the Voronoi Seabed Sedimentary Domain Boundary Reconstruction. Issue 3 (March 2020) - Zhang, Jin; Li, ShuJun; Wang, Mo
Abstract: Seabed sediment point data is the data basis for expressing the sediment elements. The determination of the extent of the seabed sediment type is the data base of the geometric model and the seabed sediment thematic chart. For the existing point element selection method cannot meet the application requirements. This paper uses the weighted idea to different data density and complex marine environment. Taking into account the trend of the sediment size and charting compensation effect, the influence weight of the point-like bottom data is analyzed, and the range of influence is reasonably determined. It provides a certain reference for the production of seabed sediment thematic chart and has high use value and broad application prospects.